Management of the School-Age Youth Guidance Program (BRUS) at MAN 1 Pasuruan: Manajemen Program Bimbingan Remaja Usia Sekolah (BRUS) di MAN 1 Pasuruan - Shodiqin, Ali; Fahyuni, Eni Fariyatul (Indonesian Journal of Innovation Studies, 2026)
General Background Early marriage remains a critical social challenge in Indonesia, resulting in adverse multidimensional consequences across health, psychological, and socioeconomic dimensions. Specific Background In response, the Ministry of Religious Affairs launched the School-Aged Youth Guidance Program (BRUS) as a school-based preventive initiative. Knowledge Gap However, existing literature primarily evaluates external implementation or outcome efficacy, leaving a gap regarding school-level managerial processes. Aims This qualitative single-case study examines the management of the BRUS program at MAN 1 Pasuruan. Results Findings reveal that implementation succeeds through participatory planning based on needs analysis, a matrix organizational structure coordinating internal and external stakeholders, an integrative execution combining educational methods with Islamic values, and data-driven monitoring and evaluation. Novelty The study establishes a comprehensive school-level management model that embeds Islamic values directly into preventive management frameworks. Implications These insights offer a strategic operational framework for Islamic secondary educational institutions to optimize early marriage prevention initiatives. Key Findings Highlights Participatory needs-based planning and a matrix organizational structure enable effective multi-stakeholder collaboration between madrasahs and local religious affairs offices. Integrating educational methodologies with core Islamic values significantly strengthens student engagement and receptivity toward early marriage prevention. Data-driven monitoring and evaluation mechanisms ensure continuous quality improvement and long-term program institutionalization within school management systems. Keywords : BRUS Program, Educational Management, Early Marriage Prevention, Islamic School Administration, Student Guidance